Regulation of Brassinosteroid Signaling and Salt Resistance by SERK2 and Potential Utilization for Crop Improvement in Rice - Dong, Nana; Yin, Wenchao; Liu, Dapu; Zhang, Xiaoxing; Yu, Zhikun; Huang, Wei; Liu, Jihong; Yang, Yanzhao; Meng, Wenjing; Niu, Mei; Tong, Hongning (Frontiers in Plant Science, 2020)
The complex roles of the steroid hormone brassinosteroids (BRs) in many different yield- and stress-related traits make it difficult to utilize the hormones for crop improvement. Here, we show that SERK2 as a BR signaling component is a potentially useful candidate for BR manipulation in rice. We generated multiple mutant alleles of SERK2 by CRISPR/Cas9 editing and show that knockout of SERK2 results in a compact structure accompanied with increased grain size. SERK2 is localized on plasma membrane and can interact with OsBRI1, the BR receptor, suggesting its conserved role as co-receptor in BR signaling. Consistently, the mutant has impaired BR sensitivity compared to wild type. Notably, the mutant is highly sensitive to salt stress as evaluated by plant survival rate as well as transcriptome analysis, whereas has slightly increased sensitivity to ABA, the stress hormone. By contrast, overexpression of SERK2 significantly enhances grain size and salt stress resistance, importantly, without affecting plant architecture. Furthermore, while salt suppresses SERK2 transcription, the protein is greatly induced by salt stress. Taken together, we propose that the adverse condition induces SERK2 accumulation to enhance early BR signaling on plasma membrane in favor of the anti-stress response. Our results illustrate the great potentials of specific BR components such as SERK2 for crop improvement by utilizing flexible strategies.